Environmental Policy and Incentives to Invest in Advanced Abatement Technology if Arrival of Future Technology is Uncertain - Extended Version - Andreas von Döllen; Till Requate (Kiel University, Department of Economics, 2007)
We study long-term incentives for polluting and regulated firms to invest in advanced abatement technologies, when some new technology is available but an even better technology will be expected in the future. Firms can invest only once. We find that depending on the adoption fixed costs all possible combinations of investment patters can occur in social optimum. Further we show that if the regulator anticipates the arrival of the new technology he can decentralize socially optimal allocation by charging Pigouvian tax or issuing tradable permits through announcing his policy and setting ex post optimal policy levels, after firms have invested.
Keywords: Q55; L5; O31; 330; Emission taxes; tradable permits; option value theory; uncertainty; Poisson distribution